Revisit intentions in local food restaurants: a critical review - Sari, Niken Permata; Tjahjono, Heru Kurnianto (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2024)
This study examines the factors influencing revisit intention at local food restaurants, emphasizing the need for a broader methodological approach. Through a critical review of relevant studies, this study identifies customer satisfaction, service quality, and food value as essential determinants of predicting revisit intention. Furthermore, this study critiques methodological approaches in the literature, highlighting limitations such as selection bias and limited sample representation due to standard non-random sampling methods. A mixed-methods approach, incorporating quantitative and qualitative data, is recommended to provide a more comprehensive understanding of diners’ motivations and experiences. Expanding sampling techniques to incorporate random or stratified methods is suggested to increase the generalizability of the findings. This approach would also allow for richer insights into how social, cultural, and technological factors influence revisit intention across contexts. Ultimately, this study contributes to a deeper understanding of the complexity of customer behavior, particularly as it relates to culinary experiences, and proposes future research directions that integrate multiple sampling and analysis methods to capture the dynamic nature of revisit intention.